Discourse on Dinsman’s contributions to the development of modern Malay theatre - Mas Rynna Wati Ahmad (Pusat Pengajian Media dan Komunikasi, Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2015)
Modern Malay theatre in the 1970s had witnessed a drastic change when Experimental Theatre was first introduced. The plays that were produced during this time had been associated with absurd plays as these plays contained strong tendencies towards the application of the absurd theatre techniques. Realizing the social and religious backgrounds of the Malays generally, the playwrights of this period tend to appropriate the typical absurd theatre techniques which were commonly practiced in the West. From the typical no resolutions plays, the experimental absurd plays have provided closures that resemble hopes and marked out any forms of pessimisms. This paper will discuss on Dinsman, as a prominent experimental playwright during the upheaval period of The Experimental Theatre in Malaysia. For the purpose of this paper, his famous experimental play, It Is Not A Suicide that was produced and staged in the 1970s is selected. The play was highly criticized not only for it was incomprehensible, but also, it was unable to disseminate good religious values to the masses. However, after a thorough discourse on this specific play, the paper had found out that, the play delves further into a metaphysical search that seeks answer through the path of religion. Therefore this paper aims to highlight his method of appropriation in creating a play that is distinctively his own. With such bold experimentations, Dinsman had led the new playwrights to continue the experimental traditions in re-creating new styles which would contribute highly not only to the Malay theatre productions generally but also to the field of Malay theatre criticisms specifically.